A Magnetohydrodynamic enhanced entry system for space transportation: MEESST. Issue 1 (March 2023) - Lani, Andrea; Sharma, Vatsalya; Giangaspero, Vincent F.; Poedts, Stefaan; Viladegut, Alan; Chazot, Olivier; Giacomelli, Jasmine; Oswald, Johannes; Behnke, Alexander; Pagan, Adam S.; Herdrich, Georg; Kim, Minkwan; et al.
Abstract: This paper outlines the initial development of a novel magnetohydrodynamic (MHD) plasma control system which aims at mitigating shock-induced heating and the radio-frequency communication blackout typically encountered during (re-)entry into planetary atmospheres. An international consortium comprising universities, SMEs, research institutions, and industry has been formed in order to develop this technology within the MEESST project. The latter is funded by the Future and Emerging Technologies (FET) program of the European Commission's Horizon 2020 scheme (grant no. 899298). Atmospheric entry imposes one of the harshest environments which a spacecraft can experience. The combination of hypersonic velocities and the rapid compression of atmospheric particles by the spacecraft leads to high-enthalpy, partially ionised gases forming around the vehicle. This inhibits radio communications and induces high thermal loads on the spacecraft surface. For the former problem, spacecraft can sometimes rely on satellite constellations for communicating through the plasma wake and therefore preventing the blackout. On the other hand, expensive, heavy, and non-reusable thermal protection systems (TPS) are needed to dissipate the severe thermal loads. Such TPS can represent up to 30% of an entry vehicles weight, and especially for manned missions they can reduce the cost- efficiency by sacrificing payload mass. Such systems are also prone to failure, putting the lives of astronauts at risk. The use of electromagnetic fields to exploit MHD principles has long been considered as an attractive solution for tackling the problems described above. By pushing the boundary layer of the ionized gas layer away from the spacecraft, the thermal loads can be reduced, while also opening a magnetic window for radio communications and mitigating the blackout phenomenon. The application of this MHD-enabled system has previously not been demonstrated in realistic conditions due to the required large magnetic fields (on the order of Tesla or more), which for conventional technologies would demand exceptionally heavy and power-hungry electromagnets. High-temperature superconductors (HTS) have reached a level of industrial maturity sufficient for them to act as a key enabling technology for this application. Thanks to superior current densities, HTS coils can offer the necessary low weight and compactness required for space applications, with the ability to generate the strong magnetic fields needed for entry purposes. This paper provides an overview of the MEESST project, including its goals, methodology and some preliminary design considerations.